IMPLEMENTATION OF KAHOOT-ASSISTED PROBLEM-BASED LEARNING MODEL TO IMPROVE NUMERACY SKILLS: A CASE STUDY OF FRACTIONAL MATERIALS - Gunawan, Gunawan; Nalim, Nalim; Rahayu, Sinta Puji; Kusuma, Jaka Wijaya (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
Numeracy skills are an important component of 21st century learning and are a reference in PISA results. This research aims to improve numeracy skills in fractional materials through a problem-based learning model assisted by kahoot media. The subject of the study was a grade VI student of SD Negeri 3 Karangtengah. The research method applied is class action research. The research was carried out in two cycles, each cycle consisting of two meetings. Each meeting consists of 4 stages, namely planning, implementation, observation/observation, and reflection. The research instruments used were numeracy skills tests and observation sheets on learning implementation. The data analysis technique used in this study is quantitative by analyzing the increase in the cycle of the numeracy test and learning observation sheets. The results of the study show that the application of the problem-based learning model assisted by kahoot media can improve students' numeracy skills. This condition is evidenced by the results of the numeracy skills test in the implementation of the first cycle, obtaining an average score of 78.75% then increasing in the second cycle by 80%. The results of the research provide scientific and practical contributions on learning innovations that are encouraging and support the improvement of learning outcomes, especially numeracy.